TRANSFORMASI KONTEN MEDIA SOSIAL SEBAGAI STRATEGI KOMUNIKASI PEMASARAN DALAM BINGKAI DAKWAH - Yunita, Mella; Hasanah, Uswatun (JURNAL SYIAR-SYIAR, 2024)
This research aims to explore the transformation of social media content as a marketing communication strategy within the framework of Islamic da'wah. The research methodology employed a literature review by analyzing relevant journal articles, books, and other scholarly publications. The main focus of the study was on the reconceptualization of da'wah elements in response to new media culture, the integration of da'wah content into social media marketing communication strategies, and the alignment of social media content transformation with the guidance of the Qur'an and the principles of Islamic law. The results of the study indicate that social media has proven to be an effective tool for disseminating da'wah messages globally, reaching a wider audience, especially Generation Z and millennials. Meaningful and peaceful da'wah content strategies, as well as collaboration among Islamic scholars, students, and wise social media users, are key to creating a positive impact in influencing public perceptions of Islam. However, the research also identified several challenges, such as the spread of inaccurate information and a lack of understanding of social media ethics. The social impact of using social media in da'wah shows significant benefits in reaching a broad audience but also highlights the need for extra caution in leveraging this platform. In conclusion, the transformation of social media content as a marketing communication strategy within the framework of da'wah makes a significant contribution to strengthening the effectiveness of Islamic da'wah in the digital era. However, achieving this goal requires wise management, good message quality, and a deep understanding of social media ethics and Islamic principles. This research is expected to provide new insights and contribute to the development of relevant and effective da'wah strategies that meet the demands of the times.